2007
DOI: 10.1189/jlb.0307183
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of murine syngeneic graft-vs.-host disease by CD4+ T cells

Abstract: Syngeneic graft-vs.-host disease (SGVHD) develops in rodents following the treatment of lethally irradiated, bone marrow (BM) reconstituted animals with a short course of the immunosuppressive agent cyclosporine A (CsA). Using an in vivo depletion approach, we recently demonstrated that CD4(+), but not CD8(+), T cells participated in inducing SGVHD. Studies were therefore undertaken to adoptively transfer SGVHD into lethally irradiated, syngeneic BM reconstituted secondary recipients. Whole T cell populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…It has been observed that proportions of CD4 ϩ T cells are increased in colons of SGVHD mice compared with BMT controls and that CD4 ϩ T cells were responsible for the induction of murine SGVHD (3,4,9). The role of CD4 ϩ T cells as effector cells in the induction of murine SGVHD was demonstrated in two sets of experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been observed that proportions of CD4 ϩ T cells are increased in colons of SGVHD mice compared with BMT controls and that CD4 ϩ T cells were responsible for the induction of murine SGVHD (3,4,9). The role of CD4 ϩ T cells as effector cells in the induction of murine SGVHD was demonstrated in two sets of experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, CD4 ϩ , but not CD8 ϩ , T cell depletion during the 21 days of CsA therapy inhibited SGVHD-induced colitis (9). Additional studies showed that murine SGVHD could be transferred to secondary recipients with CD4 ϩ , but not CD8 ϩ , T cells isolated from diseased animals (4). Given the role of CD4 ϩ T cells in the induction of SGVHD, studies were designed to follow up on the observation that CD4 ϩ T cells accumulate in the colon during CsA therapy (9) and to study potential mechanisms involved in trafficking of these cells into the colon of CsA-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations